1° Seminario Internazionale di Studi «La ricerca educativa: procedure, metodi, strumenti», 11 aprile 2011, Roma - Valeria Biasi (LED Edizioni Universitarie, 2011)
1st International Study Day «Educational Research: Procedures, Methods, Instruments» The 1st International Study Day, organized by the Journal of Educational, Cultural and Psychological Studies at the Faculty of Education Sciences of «Roma Tre» University (11 April 2011), aimed to assess the state of the art of educational research by presenting some examples of studies carried out along differentiated methodological lines. The themes dealt with by the speakers may be grouped into three main categories: (1) Interdisciplinary orientation in educational research; (2) The importance of methodological rigour; (3) The importance of «mixed methods» in educational research. In short, thanks to the analysis and reflections developed, different viewpoints meeting with an interdisciplinary perspective converged on how qualitative empirical investigation (specialised in finding meanings) and quantitative empirical investigation (geared to finding rigorous statistical results with regard to the studied phenomena), applied to the study of educational variables, thanks to a mastery of the most advanced technologies and tools available, can offer an epistemic advantage (the product of a combination of observational and correlational methods, quasi-experimental procedures, orthodox experimental procedures, and the outcomes of clinical and historical analysis) and thus represent an added value in methodological research in the educational field and beyond.